A Research on Teachers’ Views about the Metaverse Platform and Its Usage in Education - Gülşah Gürkan; Harun Bayer (Journal of Science Learning, 2023)
This study was conducted to determine primary and secondary teachers' views of the concept of "metaverse". In line with the aim of the study, a questionnaire consisting of closed and open-ended questions about the metaverse platform and its applications in the field of education was applied to 122 teachers. The results showed that approximately 65% of the teachers stated that they knew the concept of the metaverse and its applications. In addition, approximately 55% of the teachers stated that they first heard about the metaverse concept from social media, and 45% stated that they were most aware of metaverse applications in the field of play. Most teachers (69.7%) answered no about the benefits of the metaverse platform in education. Approximately 95% of the teachers stated that they wanted seminars and workshops on metaverse applications in education and wanted these studies to be mostly aimed at introducing the metaverse platform and its applications in the educational environment. Based on the study results, introductory pre-service and in-service studies can be conducted for teachers regarding the metaverse and its applications in the field of education and its possible benefits.